Potential of Elderly Caregivers Associated with Isan Cultural Context - Rattanaraj, Parichat; Sarakan, Kotchapong; Kotta, Paiwan (Journal of The Royal Thai Army Nurses, 2020)
The purposes of this descriptive research were to 1) study and compare the potential of caregivers of elderly people as Isan context in municipal and non municipal area, and 2) study the role of professional nurses for promoting competency of caregiver among elderly people. Two hundred and ten caregivers of elderly people for questionnaire, five caregivers of elderly people for in-depth interview and five professional nurses who had responsibility in elderly care service for in-depth interview were selected using multi-stage sampling. Research instruments consisted of demographic data, the potential of caregivers of elderly people questionnaire developed by researcher, reliability obtained by using Cronbach’s alpha coefficients of 0.90. Quantitative data were analyzed using frequency, percentage, mean, standard deviation and t-test. For qualitative data were analyzed using content analyses. The results of this study demonstrated that 1) Mean score of the potential of caregivers of elderly people in municipal and non municipal area at high level ( = 4.05 and 4.09), 2) The comparison of the potential of caregivers of elderly people in municipal and non municipal area were overall not different, 3) The comparison of the potential of caregivers of elderly people in municipal and non municipal area at each aspect found that mind, social and economic part were different in a statistically significant at the 0.05 level (t = -2.03, -3.12 and 3.22 as follows). Finally, professional nurses have also responsibilities to provide the individual education about caring for elderly people instead of promoting caregivers’ attitude and physical and mental care of caregivers. The results of this study indicated that caregivers both in municipal and non municipal area have the potential for providing elderly care. Healthcare provider, therefore, especially professional nurses should take responsibilities in promoting education and skills regarding elderly health care for maintaining the potential and competency among caregivers. Moreover, nurse should promote caregivers’ attitude and caring of physical and mental of caregivers.